Microstructure and electric properties of Pr-doped Pb(Zr0.52Ti0.48)O3 ceramics - Zou, Lingfang; Li, Zhuan; Gao, Zonglong; Chen, Fu; Li, Wenjie; Yu, Yong; Li, Yimin; Xiao, Peng (Ceramics international, 2021)
Improving the piezoelectric activity of lead zirconate titanate (PZT) ceramics is of great importance for practical applications. In this study, the influence of Pr3+ doping on the ferroelectric phase composition, microstructure, and electric properties on the A-site of (Pb1-1.5xPrx)(Zr0.52Ti0.48)O3 is extensively investigated. A dense and fine microstructural sample is obtained with the introduction of Pr3+. The results show that the morphotropic phase boundary (MPB) moves to the rhombohedral phase region. The rhombohedral and tetragonal phases exhibit an ideal coexistence in the 4 mol.% Pr3+ doped (PPZT4) samples. Lead vacancy and the reduction of the potential energy barrier are considered to be the key mechanisms for donor doping, which is upheld by the Pr3+ doping. Combining the I-E hysteresis loops with the P-E hysteresis loops, it becomes apparent that both contribution maximums of the domain switching and residual polarisation are in PPZT4. Moreover, the thermal aging resistance of PZT is improved by doping, and the temperature stability is optimised from 83% in PZT to 96% in PPZT4. Hence, an appropriate amount of Pr3+ doping can effectively improve the piezoelectric activity of PZT ceramics in the MPB area and optimise the performance stability of the material under application temperatures.